Aid and the political economy of policy change - Killick, Tony. (London ; New York : Routledge, 1998)
This volume looks at the effectiveness of conditionality in structural adjustment programmes. Tony Killick charts the emergence of conditionality, and challenges the widely held assumption that it is a cooperative process.
Machine generated contents note: 1. practice and justification of conditionality -- 2. What has adjustment conditionality achieved? -- 3. Conditionality and adjustment in South-east Asia and Latin America / Ramani Gunatilaka / Ana Marr -- 4. 'ownership' problem -- 5. model, the research, some results -- 6. Rewards, punishments and the influence of national politics -- 7. Alternatives to conditionality.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Economic assistance; Structural adjustment (Economic policy); Economic history -- 1971-1990.; Economic history -- 1990-; Aide économique.; Ajustement structurel (Économie); Histoire économique -- 1971-1990.; Histoire économique -- 1990-; assistance; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; Economic assistance; Economic history; Structural adjustment (Economic policy); Since 1971